Unexpected foreign body in the leg of an 8-month-old child. (10th July 2014) - Duymuş, Tahir Mutlu; Mutlu, Serhat; Turan, Enver; Mutlu, Harun
Abstract : Accidents and injuries associated with foreign bodies are important causes of childhood mortality. Diagnosis can be facilitated by obtaining a detailed history, performing a physical examination and utilising simple imaging methods. We report a case involving a fragmented sewing needle in the left leg of an 8-month-old male infant. He was admitted to our clinic with diffuse pain in the left leg, limitation of leg movements and an inability to stand. The patient was successfully treated with open surgery under fluoroscopy. Soft tissue foreign bodies and potential child physical abuse should be considered in children with ambiguous symptoms and unusual skin lesions. Parents should be educated on prevention of household accidents involving children. Penetration of sewing needles into the body has been rarely reported in the literature. We thus report this case to draw attention to the complications and morbidity associated with a delayed diagnosis in such cases.